(Invited) The U.S. Department of Energy's Energy Materials Network. (7th July 2017) - Sarkar, Reuben; Miller, Eric L.; Vickers, James W; Randolph, Katie; Joost, William; Fitzgerald, Nichole; Craig, Kevin; Olson, Dana; Trinastic, Jonathan; Litombe, Nicholas
Abstract : Affordable, reliable, high performance materials and manufacturing technologies are key for transformational technology advancements in critical domestic energy applications. However, many materials discoveries in the laboratory either never reach widespread market deployment or spend decades in the development cycle at an extremely high cost. In response, the U.S. Department of Energy has established the Energy Materials Network (EMN) to accelerate the materials-to-market process by better integrating the stages from materials discovery through qualification. The EMN is a network of National Lab-led consortia that support both industry-guided and government-led research on specific energy-related material challenges. The EMN framework facilitates industry stakeholder engagement to ensure that research is immediately relevant, with high-impact commercial potential. To date, EMN consortia have been set up in seven technology areas. This paper describes the vision of the EMN as an enduring national resource, and discusses recent accomplishments in the current network of EMN consortia.